TERRITORIAL CONSOLIDATION OF THE REPUBLIC OF MOLDOVA: PROBLEMS, STRATEGIES AND CHALLENGES - Mihai ROSCOVAN; Andrei RUSSU; Corneliu GUTU (Economica)
Te Republic of Moldova is currently facing significant problems in terms of public administration, such as excessive bureaucracy, corruption, and low efficiency of public services. At the same time, there is a significant discrepancy between rural and urban areas, which negatively affects citizens’ access to public services delaying social and territorial cohesion. In this regard, analysing ways to optimize the administrative and territorial structure can be an important step in identifying the necessary administrative tools to improve citizens’ access to quality public services. This article proposes an analysis of the problems in the existing system of administrative-territorial organization in the Republic of Moldova and presents some visions on implementing the reform for territorial consolidation.